Determinants of COVID-19 vaccine acceptance among adults with diabetes and in the general population in Israel: A cross-sectional study. (July 2022) - Kolobov, Tatyana; Djuraev, Simcha; Promislow, Sara; Tamir, Orly
Highlights: Diabetes patients were more concerned about getting COVID-19 than the general public. Diabetes patients were more concerned about vaccine safety than the general public. Male diabetes patients were ∼6 times more likely to vaccinate than female patients. Abstract: Aims: To explore and compare key determinants of COVID-19 vaccine acceptance and willingness to get vaccinated among people with diabetes and the general population. Methods: A cross-sectional survey study of 807 Israeli adults with and without diabetes was conducted prior to the first vaccination campaign in Israel in December 2020. Data was analyzed by population group and gender. A multinomial logistic regression determined the association between acceptance factors and willingness to get vaccinated. Results: Diabetes patients had more anxiety about COVID-19, higher levels of confidence in vaccine safety, and greater willingness to get vaccinated than the general population. In both groups, women reported higher levels of anxiety toward COVID-19 but lower levels of confidence in vaccine safety and less willingness to get vaccinated than men. Vaccine safety had the largest contribution to diabetes patients' willingness to get vaccinated. For participants without diabetes, the perception that more than 50% of Israelis would get vaccinated had the largest contribution. Participants in both groups who had vaccinated against seasonal influenza were more likely to get vaccinated against COVID-19. Conclusion: Policies aimed at improving vaccine acceptance should target vulnerable populations, particularly female diabetes patients, whose concerns must be addressed to increase their vaccination rates.